The impacts of social media advertisement on consumer purchase behavior among generation z - Khor, Xin Tian (2023)
The prevalence of social media platforms has made it a significant channel for businesses to reach consumers. In this study, the primary objective is to investigate the impacts of social media advertisement on consumer purchase behavior among Generation Z. With this aim, empirical data were collected through self-administered questionnaires from a convenience sample of 150 respondents who reside in Malaysia and had prior experience with social media platforms. Proposed hypotheses were tested using the Statistics Package for Social Sciences (SPSS). In this respect, the study employs the Uses and Gratification Theory (UGT) as the theoretical basis to investigate the impacts of entertainment, informativeness, irritation, credibility, and electronic word of mouth on consumer purchase behavior among Generation Z. The findings of this study reveal that entertainment, credibility, and electronic word of mouth have a significant positive relationship on consumer purchase behavior among Generation Z. However, the study found that irritation has a negative impact on consumer purchase behavior among Generation Z towards social media advertisement. Moreover, the empirical findings also supported the impact of entertainment, irritation, credibility, eWOM towards social media advertisement on purchase behavior among generation Z. The study concludes with a discussion of the implications for marketers and businesses to develop effective social media advertising strategies to target Generation Z. At the end of the study, it provides insights into the factors that influence the purchase behavior of Generation Z in response to social media advertising and offers useful implications for businesses seeking to target this consumer segment.